Does neoadjuvant chemotherapy reduce surgical complexity in patients with advanced-stage epithelial ovarian cancer? - Okan Aytekin; Simge Kirmizigul Kerinc; Abdurrahman Alp Tokalioglu; Yesim Ozkaya Ucar; Fatih Kilic; Gunsu Kimyon Comert; Gokhan Ucar; Burak Civelek; Taner Turan (BMC, 2024)
Abstract Background This study aimed to determine the effect of neoadjuvant chemotherapy (NACT) on the complex surgical procedures required in addition to staging surgery for the need to achieve a residual tumor 1 cm or less in a population of stage IIIC-IV epithelial ovarian cancer patients. Methods Patients were referred for NACT if preoperative imaging and/or intraoperative evaluation confirmed that it was not possible to achieve a residual tumor size of 1 cm or less with cytoreductive surgery or if the patient had a poor performance status and a high American Society of Anesthesiologists (ASA) score. Surgical complexity was defined as complex or non-complex. Results One hundred and twenty-six patients with stage IIIC-IV ovarian cancer were included in the study. Primary cytoreductive surgery was performed in 67 patients, and interval cytoreductive surgery was performed in 59 patients after NACT. At least one complex surgery was performed in 74.6% of the patients in the primary cytoreductive surgery group and in 61% of the patients in the NACT group, with no statistically significant difference between the groups. However, the NACT group showed significantly decreased rates of low-rectal resection, diaphragmatic peritoneal stripping, and peritonectomy. Conclusions The analyses showed no reduction in the requirement for at least one complex surgical procedure in the group of patients who underwent NACT. Nevertheless, this group exhibited a significant decrease in low-rectal resection, diaphragmatic peritoneal stripping, and peritonectomy due to their effectiveness in reducing peritoneal disease.